Collecting, managing and translating data into National Action Plans for artisanal and small scale gold mining. Issue 1 (January 2020) - Stylo, Malgorzata; De Haan, Jorden; Davis, Kenneth
Highlights: Comprehensive national overview of the ASGM is a foundation for designing an effective National Action Plan for the sector. The tension between the informality of mining operations and formality of interventions is one of the barriers to retrieve reliable data. Obtaining reliable data from foreign-owned small-scale operations poses a challenge for developing accurate baseline estimates of mercury use. Engagement of the local stakeholders early in the process of the NAP development lays the groundwork for the successful implementation. In Sierra Leone, the sector is important not only for combating poverty, but also for promoting education and empowering women. Abstract: Countries developing National Action Plans for artisanal and small-scale gold mining under the Minamata Convention on Mercury require a comprehensive understanding of the sector to produce effective strategies for reducing mercury use and realizing the sector's sustainable development potential. In order to gain this understanding, they must first analyse available information and collect new data. This paper provides an overview of the approaches countries are taking as part of their National Action Plan projects and features a case study from Sierra Leone that contextualizes the process of data collection and analysis. The paper identifies the tension between the typical informality of mining operations and the formality of government interventions as the main impediment to retrieving reliable environmental, socio-economic and health information and accurately estimating mercury use in the sector, both of which are instrumental for setting comprehensive strategies and realistic mercury reduction targets under the Minamata Convention. It further recommends an inclusive and participatory approach to enable the effective implementation of the strategies, with the aim to unlock the sector's full potential to diversify and strengthen local economies, empower local communities, and at the same time, protect human health and the environment.